2016
DOI: 10.1182/blood-2015-09-670034
|View full text |Cite
|
Sign up to set email alerts
|

A subset of high-titer anti–factor VIII A2 domain antibodies is responsive to treatment with factor VIII

Abstract: • Discrepancies exist between inhibitor titer and bleeding phenotype in anti-fVIII antibodies.• A subset of high-titer type 2 anti-A2 inhibitors can be treated with fVIII.The primary B-cell epitopes of factor VIII (fVIII) are in the A2 and C2 domains. Within the C2 domain, antibody epitope and kinetics are more important than inhibitor titer in predicting pathogenicity in a murine bleeding model. To investigate this within the A2 domain, the pathogenicity of a diverse panel of antihuman fVIII A2 domain monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…Anti-FVIII mAbs directed against non-C1 domain VWF epitopes increase FVIII clearance in FVIII À/À mice Previously we investigated the in vivo pathogenicity of antibodies against the A2 and C2 domains of FVIII [14,15]. A subset of anti-A2 and C2 mAbs produced bleeding in FVIII À/À mice at low and high doses of FVIII (180 units kg À1 and 360 units kg À1 , respectively) in the tail snip bleeding model.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-FVIII mAbs directed against non-C1 domain VWF epitopes increase FVIII clearance in FVIII À/À mice Previously we investigated the in vivo pathogenicity of antibodies against the A2 and C2 domains of FVIII [14,15]. A subset of anti-A2 and C2 mAbs produced bleeding in FVIII À/À mice at low and high doses of FVIII (180 units kg À1 and 360 units kg À1 , respectively) in the tail snip bleeding model.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, assays of this nature can be time‐consuming and undertaken in laboratories outside a diagnostic centre, and inhibitor titres in patients with acquired HA may not predict prognosis . In addition, Eubanks et al . reported that a one‐stage clotting assay for residual FVIII:C appeared unlikely to reflect the inhibitory effects of some FVIII monoclonal antibodies on coagulation function.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies were purchased from Fisher Scientific (CD41, NB100-2614, 1:400), Santa Cruz Biotechnology (P-selectin, sc-19996, 1 µg ml −1 ), Bio-Rad (vWF-FITC, AHP062F, 1:1000), BD (CD45, 555483, 1:400), and abcam (TF, ab35807, 1:200). Antibody AVW-3 and 59D8 (Alexa Fluor 488 conjugated) were provided by Dr. Shawn M. Jobe (Blood Center of Wisconsin, 10 µg ml −1 , 1:100) and mAb 2–76 by Dr. Shannon L. Meeks (Emory University, 10 µg ml −1 ) 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%